1996
DOI: 10.1136/vr.139.3.64
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for perinatal and postnatal mortality in lambs

Abstract: Factors associated with preweaning mortality in lambs were identified by developing risk profiles with logistic regressions for perinatal and postnatal mortality. Compared with heavy lambs, lambs of low birth weight had almost twice the risk of perinatal mortality (odds ratio [OR] = 1.9) and lambs of average weight had a slightly lower risk (OR = 0.7). Two of four lambing location categories affected perinatal mortality, with lambs born at unmonitored areas at greatest risk (OR = 2.7). Multiple births increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 11 publications
7
37
1
1
Order By: Relevance
“…However, for the lambs that died at birth and had sex recorded the ratio of males to females was 1 : 2, which follows published literature (Dalton et al, 1980;Morris et al, 2000). This is probably mostly due to its effect on birth weight (Nash et al, 1996;Holst et al, 2002). The effect of age of ewe on lamb mortality has been shown by many authors to be important; often reported to generally decline with age up to the fourth or fifth parities (Dalton et al, 1980;Morris et al, 2000;Sawalha et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…However, for the lambs that died at birth and had sex recorded the ratio of males to females was 1 : 2, which follows published literature (Dalton et al, 1980;Morris et al, 2000). This is probably mostly due to its effect on birth weight (Nash et al, 1996;Holst et al, 2002). The effect of age of ewe on lamb mortality has been shown by many authors to be important; often reported to generally decline with age up to the fourth or fifth parities (Dalton et al, 1980;Morris et al, 2000;Sawalha et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have postulated that increased lamb mortality in males may be due to differences in birth weight (Smith, 1977;Gama et al, 1991;Nash et al, 1996). In the present study, however, greater lambing difficulty and mortality were still evident in male lambs even after adjusting for gender differences in birth weight.…”
Section: Risk Factors Associated With Lambing Gendercontrasting
confidence: 54%
“…Moreover, the proportion of lambs dying from infection was largest in twin and triplet litters. Mastitis, which is associated with reduced milk production and quality, or poor milk production per se, might result in inadequate milk supply to the lambs and increase the risk of lamb mortality, particularly in lambs from litters of multiples (Nash et al, 1996;Arsenault et al, 2008). The sampling performed in the present study was completed before the earliest reports of Schmallenberg virus in central Europe (Hoffmann et al, 2012;van den Brom et al, 2012) and thus this virus is unlikely to have caused congenital malformations detected in this study.…”
Section: Discussionmentioning
confidence: 99%